Production and characterization of sophorolipid under yeast-mediated submerged fermentation utilizing Agro-industrial waste - Aishwary Purohit; Amar Jyoti Das; Debashish Ghosh (Current Research in Microbial Sciences)
The challenges of pollution and agro-industrial waste management have led to the development of bioconversion techniques to transform these wastes into valuable products. This has increased the focus on the sustainable and cost-efficient production of biosurfactants from agro-industrial waste. Hence, the present study investigates the production of sophorolipid biosurfactants using the yeast strain Rhodotorula mucilaginosa IIPL32 under submerged fermentation, employing sugarcane bagasse hydrolysate—a renewable, low-cost agro-industrial waste as the feedstock. By systematically optimizing strain adaptation, medium composition, and scaling up the process from shake flasks to a bioreactor, a maximum sophorolipid yield of 2.6 ± 0.21 g/L was achieved. Extensive characterization was conducted, encompassing emulsification index (54 %), surface tension reduction, and several chemical analyses (anthrone, iodine, saponification, lipid solubility). Advanced structural elucidation techniques such as Fourier-transform infrared (FTIR) spectroscopy, liquid chromatography-mass spectrometry (LC-MS), and nuclear magnetic resonance (NMR) spectroscopy were employed for structural confirmation of the extracted biosurfactant. FTIR spectroscopy identified characteristic functional groups, while LC-MS revealed distinct sophorolipid congeners with varying lipid chain lengths and acetylation. NMR spectroscopy corroborated the presence of disaccharide and fatty acid components, indicating the extracted biosurfactant might be sophorolipid. This study underscores the feasibility of utilizing agro-industrial waste for the eco-friendly production of sophorolipid biosurfactants and provides detailed insights into their structural features, highlighting their potential applications across diverse fields such as pharmaceuticals, cosmetics, and environmental remediation.